MODULARITY AND VARIETY SPINOFFS: A SUPPLY CHAIN PLANNING PERSPECTIVE - Medini, Khaled (International Journal of Industrial Engineering: Theory, Applications and Practice, 2016)
Rising customer demand for customized products induces an increasing complexity on the side of manufacturing firms and their supply chains. Such complexity goes hand in hand with increasing costs and lead times of customer order fulfilment process. Product modularity is a common way to cope with diversified demands while reducing costs and lead times. This paper proposes a linear programming model for assembly supply chain planning considering product variety and supply chain operations costs. The model is used to analyze the impact of modularity on the economic performance of a fictive assembly firm in the field of electronic equipment, which is inspired by a real case. Several insights are drawn from the illustrative example. For instance, the model turns out to be very useful in identifying trade-offs between customer demand for variety and respective costs incurred by the enterprise.